Adsorption of -Nitrophenol onto PDMDAAC-Modified Bentonites - Xianjia Peng; Zhaokun Luan; Hongmei Zhang; Binghui Tian; Bin Fan (Adsorption Science & Technology)
A novel organobentonite was prepared by modifying bentonite with poly(dimethyldiallylammonium chloride) (PDMDAAC), a harmless and cost-effective type of polycation. Zeta potential and X-ray diffraction measurements suggest that PDMDAAC was intercalated into the bentonite interlayer space. PDMDAAC—bentonite has been found to be effective for the removal of p -nitrophenol with a removal rate of 81.4% being achieved. The adsorption process was pH-dependent and was slightly decreased by the Ca 2+ and Mg 2+ ions co-existing in the solution. A dual-phase adsorption mechanism was suggested for the process. The adsorbents obtained from the regeneration of PDMDAAC—bentonite still exhibit good adsorption capacities.